A Systematic Review on Radon Interventions around the Globe - Selim M. Khan; James Gomes; Daniel R. Krewski (Current Advances in Geography, Environment and Earth Sciences Vol. 5, 2022)
This paper systematically reviewed both experimental and observational studies (S) with radon in- terventions (I) used globally in residential houses (P) compared to other residential or model houses (C) to evaluate relative mitigation effectiveness (O) that could guide selecting the best radon reduction strategy for residential buildings. In cold countries, radon is the predominant source of environmental radiation exposure, providing a significant human health risk. By 2017, most provinces in Canada had amended their building codes to require radon-free construction in all new buildings. While numerous building solutions and remediation procedures have been developed and examined, the optimal way for effectively reducing radon in a number of environments has yet to be determined. Builders, property managers, homeowners, and residents, as well as radon practitioners, officials of radon control programmes, and businesses offering radon testing and mitigation services, have comparable questions. This review of evidence on the effectiveness of radon interventions did not involve human subjects. We selected both experimental and observational studies with radon interventions. Geographically, we included studies mainly from Europe and North America but also considered suitable studies conducted in other cold countries. Interventions in residential and model houses were included, but studies piloted purely in the lab were excluded; the PRISMA checklist was used to synthesize data; Cochrane and Hamilton tools were used to evaluate study quality. Various building solutions, radon mitigation, and remediation technologies with varying levels of success have been explored in studies all around the world. In most situations, active ventilation with a sub-slab or sump depressurization system (SSDS) was found to be more effective than passive measures such as sealing, membrane, block and beam, simple ventilation, or filtration in attaining a considerable and sustained radon decrease. The best technique is determined by a number of parameters, including the starting radon level, entry routes, building design and age, as well as various geologic, atmospheric, and climatic circumstances. This review noted that many countries with high radon areas around the globe start recognizing the importance of healthy indoor atmosphere more rapidly in recent years than ever as evidenced by their adoption of new building codes in the legislation. This requires builders to install a passive radon impermeable membrane in between the basement slabs during all new constructions to prevent radon entry from the soil to residential buildings. Although an active SSDS is the best mitigation systems, at places, it needs to be combined with another system and installed by a trained radon professional considering the pertinent factors to ensure radon level continues to remain below the action level. This study did not conduct any economic evaluation of the mitigation measures. For the practical implementation of radon mitigation, training of the construction industry, information provision for residents, the establishment of public funds, incorporation of radon-prone areas in the land utilization maps, and enacting building codes deemed essential.